Risk factors for leptospirosis seropositivity in slaughterhouse workers in western Kenya - Cook, Elizabeth A.J.; Glanville, William A. de; Thomas, Lian F.; Kariuki, S.; Bronsvoort, B.M. de C.; Fèvre, Eric M. (BMJ, 2017)
Objectives Leptospirosis has been documented in slaughterhouse workers around the world. Risk factors include smoking and drinking at work, and performing tasks such as cleaning offal. This paper examined risk factors for leptospirosis seropositivity in slaughterhouse workers in western Kenya. Methods The study was conducted between May 2011 and October 2012. Questionnaires were used to collect information from workers on demographic data, health and hygiene practices in the slaughterhouse. A commercial ELISA detected antibodies to Leptospira spp. in serum samples and multilevel logistic regression analysis identified factors associated with leptospirosis seropositivity. Results A total of 737 workers from 142 slaughterhouses were recruited. The seroprevalence of antibodies to Leptospira spp. was 13.4% (95% CI 11.1% to 16.1%). Risk factors included: having wounds (OR 3.1; 95% CI 1.5 to 6.1); smoking (OR 1.8; 95% CI 1.1 to 2.9); eating at work (OR 2.1; 95% CI 1.2 to 3.6); cleaning the offal (OR 5.1; 95% CI 1.8 to 15.0); and having a borehole for personal water use (OR 2.3; 95% CI 1.1 to 4.7). At the slaughterhouse level, risk factors included having a roof (OR 2.6; 95% CI 1.2 to 5.6) and drawing water from a well (OR 2.2; 95% CI 1.2 to 4.0). Protective factors included working in slaughterhouses where antemortem inspection was conducted (OR 0.6; 95% CI 0.4 to 1.0) and where workers wore protective aprons (OR 0.4; 95% CI 0.2 to 0.7). Conclusions This is the first report of leptospirosis seropositivity in slaughterhouse workers in Kenya. Potential risk factors were identified and this information can be used to educate workers regarding their disease risks and ways to prevent or reduce transmission.